2002
DOI: 10.1046/j.1440-6047.2002.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxalate content and calcium binding capacity of tea and herbal teas

Abstract: Thirty-two commercially available teas consisting of green, oolong and black teas were bought from supermarkets in Christchurch, New Zealand in June 2001. Fifteen herbal teas were also purchased at the same time. The soluble oxalate content of the infusate made from each of the teas was determined using high pressure liquid chromatography. The mean soluble oxalate contents of black tea in tea bags and loose tea leaves were 4.68 and 5.11 mg/g tea, respectively, while green teas and oolong tea had lower oxalate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 11 publications
(11 reference statements)
2
29
0
2
Order By: Relevance
“…McKay et al (1995) showed that steeping tea for different times and stirring the tea had a significant effect on the oxalate content of the final extraction. From their data a regular tea drinker consuming six cups of tea per day would consume between 65 and 124 mg soluble oxalate per day, which is comparable to the results obtained in the study carried out by Charrier et al (2002). If black tea is taken with added milk or is consumed with calcium-containing meals then less oxalate will be absorbed as some soluble oxalate extracted from the tea leaves will bind to calcium and continue down the digestive tract without being absorbed (Massey, 2000).…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…McKay et al (1995) showed that steeping tea for different times and stirring the tea had a significant effect on the oxalate content of the final extraction. From their data a regular tea drinker consuming six cups of tea per day would consume between 65 and 124 mg soluble oxalate per day, which is comparable to the results obtained in the study carried out by Charrier et al (2002). If black tea is taken with added milk or is consumed with calcium-containing meals then less oxalate will be absorbed as some soluble oxalate extracted from the tea leaves will bind to calcium and continue down the digestive tract without being absorbed (Massey, 2000).…”
Section: Introductionsupporting
confidence: 58%
“…Over 24 h there was a highly significant (P < 0.01) reduction in oxalate output when milk was consumed with the two teas. Charrier et al (2002) showed that a regular tea drinker consuming six cups of tea=day would have an intake of between 17.9 and 93.7 mg soluble oxalate=day from black tea in tea bags. While this intake of oxalate would occur on a daily basis these amounts are modest when compared to the soluble oxalate content of some common foods (Noonan & Savage, 1999;Albihn & Savage, 2001b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxalates can be determined by various analytical methods, such as: KMnO 4 titration [7], high-performance liquid chromatography (HPLC) with UV detection [8], HPLC with enzymatic detection [9], capillary electrophoresis [10], ion chromatography [11], chemiluminescence [12] and spectrophotometry NIR [13].…”
mentioning
confidence: 99%